STUDI DESKRIPTIF TENTANG FAKTOR-FAKTOR RISIKO TERJADINYA STROKE DI RUANG STROKE CORNER BRSU TABANAN TAHUN 2015 - Luh Gede Nita Sri Wahyuningsih; Ni Putu Kamaryati (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Background:Stroke is a brain attacks caused by blockage or rupture of brain blood vessels. Until now, stroke is unknown causes. Some risk factors may effect in increasing of stroke incidence.Aim: This study aimed to determine the risk factors influenced incident of stroke in the Stroke Corner, Tabanan Hospital.Methods: This research was a retrospective descriptive study involved 172 patients who had been treated in Stroke corner. Data were collected by chart-reviewed. Further, data were analyzed descriptively using SPSS for windows 17.0.Results: Findings found that majority of respondents aged over 65 years (39%) with male (53.5%). The results of this study also showed that there were three of highest risk factors influenced stroke incident such as hypertension (41.2%), diabetes mellitus (15.1%), and cardiac problem (7.6%).Conclusion: Although the cause of stroke is unknown but several factors such as hypertension, diabetes and heart problems greatly contribute to the incidence of stroke. Therefore, it is essential for health personnels to be more focused in managing risk factor for recurrent stroke prevention.